Evaluation of patient's knowledge level towards rationality of analgesic swamedication drug use in pharmacy x Batam city - Mevy Trisna; Renatalia Fika; Budi Setiawan; Yonrizon; Vera Triciana (Institute of Computer Science (IOCS), 2023)
Pain is the body's defense mechanism that arises when there is tissue damage, this will cause individuals to react by moving the pain stimulus. Pain can be a problem if the pain is not treated immediately, so that the disease becomes prolonged and can harm the sufferer. Various efforts have been made by humans to relieve pain. With the act of self-medication (self-medication), knowledge and understanding of the rational use of drugs are needed in carrying out self-medication. Identification of the level of patient knowledge of the rational use of analgesic self-medication drugs at Pharmacy X Batam City using descriptive observation method by purposive sampling. Based on univariate analysis, the results of the questionnaire were classified as sufficient with a percentage of 44% and the majority of respondents used drugs rationally 58% and irrationally 42%.